Accelerating European electronic health record exchange format (EEHRxF) implementation across Europe: a policy perspective - da Silva Carvalho, Nathan; Papadimitriou, Alexia; Stegwee, Robert; Gille, Hans; Strübin, Michael; Maes, Christophe; Cangioli, Giorgio; Chronaki, Catherine (Frontiers in Medicine, 2025)
BackgroundThe European Health Data Space Regulation (EHDS), published in the Official Journal since 5 March 2025, requires Electronic Health Record (EHR) systems across the European Union (EU) to adopt harmonized interoperability and logging components using the European EHR Exchange Format (EEHRxF).What is at stakeThe EHDS has come into force and the deadlines for implementation acts are approaching, Clarity on scope, obligations, and implementation options is needed to meet these deadlines.Policy optionsThis article examines ways to accelerate EEHRxF adoption, including hybrid implementation models, and coordinated national and EU-level support.RecommendationsUtilize the European EHRxF Standards and Policy Hub, align national and regional strategies, support SMEs and providers with guidance and funding, and promote digital health literacy to ensure effective EEHRxF implementation.